Who owns you? : science, innovation, and the gene patent wars - Koepsell, David R. (David Richard); Ohio Library and Information Network (Chichester, West Sussex, UK ; Malden, MA : John Wiley & Sons Ltd, 2015)
The 2nd Edition of Who Owns You, David Koepsell's widely acclaimed exploration of the philosophical and legal problems of patenting human genes, is updated to reflect the most recent changes to the cultural and legal climate relating to the practice of gene patenting. Lays bare the theoretical assumptions that underpin the injustice of patents on unmodified genes Makes a unique argument for a commons-by-necessity, explaining how parts of the universe are simply not susceptible to monopoly claims Represents the only work that attempts to first define the nature of the genetic objects involved
Individual and collective rights in genomic data : preliminary issues -- Ethics and ontology : a brief discourse on method -- The science : genes -- DNA, species, individuals, and persons -- Legal dimensions in gene ownership -- BRCA 1 and 2 : the myriad case and beyond -- Are genes intellectual property? -- DNA and the commons -- Pragmatic considerations of gene ownership -- Nature, genes and the scientific commons : a social ontology of invention -- So, who owns you? : some conclusions about genes -- Property, and personhood
Previous edition has subtitle: the corporate gold-rush to patent your genes
Includes bibliographical references and index
Keywords: Genes -- Patents; Human genetics -- Law and legislation; Intellectual property -- Moral and ethical aspects; Personality (Law); Genetics, Medical -- legislation & jurisprudence; Patents as Topic -- legislation & jurisprudence; Ownership -- ethics; Electronic books